Editorial: New Perspectives on Food Democracy - Bornemann, Basil (2019)
With the overall intention of stimulating the debate on food democracy, this thematic issue aims to shed fresh light on the complex relationship between food and democracy in different contexts. New theoretical perspectives and empirical analyses are presented that explore, sharpen, question, and expand the potential of food democracy as both, an analytical lens onto the state and development of contemporary food systems, and as a political idea for transforming the dominant agri-industrial food system. In this editorial to the thematic issue “New Perspectives on Food Democracy,” we briefly recapitulate the existing debate on food democracy, explain the goals and overarching questions of the thematic issue and provide an overview of the assembled articles.